Protein-conjugated microbubbles for the selective targeting of S. aureus biofilms - Jack A. Caudwell; Jordan M. Tinkler; Ben R.G. Johnson; Kenneth J. McDowall; Fayez Alsulaimani; Christian Tiede; Darren C. Tomlinson; Steven Freear; W. Bruce Turnbull; Stephen D. Evans; Jonathan A.T. Sandoe (Biofilm, 2022)
Staphylococcus aureus (S. aureus) is an important human pathogen and a common cause of bloodstream infection. The ability of S. aureus to form biofilms, particularly on medical devices, makes treatment difficult, as does its tendency to spread within the body and cause secondary foci of infection. Prolonged courses of intravenous antimicrobial treatment are usually required for serious S. aureus infections. This work investigates the in vitro attachment of microbubbles to S. aureus biofilms via a novel Affimer protein, AClfA1, which targets the clumping factor A (ClfA) virulence factor – a cell-wall anchored protein associated with surface attachment. Microbubbles (MBs) are micron-sized gas-filled bubbles encapsulated by a lipid, polymer, or protein monolayer or other surfactant-based material. Affimers are small (∼12 kDa) heat-stable binding proteins developed as replacements for antibodies. The binding kinetics of AClfA1 against S. aureus ClfA showed strong binding affinity (KD = 62 ± 3 nM). AClfA1 was then shown to bind S. aureus biofilms under flow conditions both as a free ligand and when bound to microparticles (polymer beads or microbubbles). Microbubbles functionalized with AClfA1 demonstrated an 8-fold increase in binding compared to microbubbles functionalized with an identical Affimer scaffold but lacking the recognition groups. Bound MBs were able to withstand flow rates of 250 μL/min. Finally, ultrasound was applied to burst the biofilm bound MBs to determine whether this would lead to biofilm biomass loss or cell death. Application of a 2.25 MHz ultrasound profile (with a peak negative pressure of 0.8 MPa and consisting of a 22-cycle sine wave, at a pulse repetition rate of 10 kHz) for 2 s to a biofilm decorated with targeted MBs, led to a 25% increase in biomass loss and a concomitant 8% increase in dead cell count. The results of this work show that Affimers can be developed to target S. aureus biofilms and that such Affimers can be attached to contrast agents such as microbubbles or polymer beads and offer potential, with some optimization, for drug-free biofilm treatment.